Modeling the Mediating Role of Taqwa in Halal Food Purchasing Behavior Using the BDI Framework - Halisa, Nur; Razak, Syaparuddin; Keri, Ismail (Journal of Economics and Social Sciences (JESS), 2025)
Introduction/Main Objectives: Halal packaged food is a growing market segment, particularly among middle-class consumers who value religious and ethical considerations. This study examines the role of taqwa (spiritual consciousness) in influencing purchasing decisions for halal packaged food and its mediating role between intention and behavior. Methodology: Using the BDI (Belief, Desire, Intention) model, this study identifies how taqwa impacts purchasing decisions. A quantitative survey was conducted with 152 middle-class respondents, and structural analysis was used to examine the relationships between variables. Findings: The results show that taqwa significantly influences halal packaged food purchasing decisions. Belief and desire shape purchase intentions, with taqwa acting as a mediator. These findings highlight the importance of taqwa in shaping consumer behavior and suggest that spirituality plays a crucial role in halal product decisions. Conclusion: The study emphasizes the need for producers and marketers to address spiritual values in halal product marketing. By aligning their strategies with consumers' spiritual and functional needs, businesses can build stronger trust and engagement, enhancing their position in the halal market.